Assessment Scale For Trainee Self-concept In The Portuguese Navy: Psychometric Properties - Frade, Ana (2017)
In this study the Assessment Scale for Trainee Self-concept in the Portuguese Navy (ASTSC-PN) was adapted to the military context. The psychometric properties are presented and the results from the factor analysis displayed, which highlighted five significant dimensions: interpersonal relationships, competence, satisfaction, selfacceptance, and risk acceptance, with an item distribution coherent with the Teacher Self-concept Evaluation Scale (Veiga, Gonçalves, Caldeira, & Zuniga, 2006). The sample involved 149 trainees of the Training Course for Petty Officers 1st Class of the Portuguese Navy, ages ranging from 25 to 36, mostly of male gender. When studying external validity the scale factors appeared correlated, as expected, with other variables of commitment with training tasks, assessed with Assessment Scale for Trainee Engagement in the Portuguese Navy (ASTE-PN) and Utrecht Work Engagement Scale (UWES), and with other variables of learning motivation, assessed with Learning Motivation Scale (LMS). The results suggest that the adapted version presents good psychometric qualities, which makes it useful in research and intervention, in psychology and education within a military context.